Índice de masa corporal en el desarrollo de la fuerza en los estudiantes de octavo y noveno año de educación básica de la Unidad Educativa García. - Richard Oswaldo, Jiménez Yánez (2023)
The present study aims to analyze the relationship between body mass index (BMI) and strength development in eighth and ninth-grade students at Garcia Educational Unit. A quasi-experimental design was employed with two independent groups, each consisting of the entire eighth and ninth-grade student populations. Pretest and post-test assessments were conducted after a 12-week period to evaluate BMI and strength. Before commencing the training program, the BMI of both groups was measured. Among the 23 eighth-grade students, 18 had a healthy BMI, 3 were at risk of overweight, and 2 were in the overweight or obese category. In the ninth-grade group, comprising 14 students, 11 had a healthy BMI, 2 were prone to obesity, and 1 was overweight. The strength endurance capacity was also assessed through a one-minute push-up test before the post-test. The mean repetitions for the eighth grade were 3,26, while for the ninth grade, it was 4,29. Upon completion of the training program, post-test results indicated that both groups experienced changes in BMI and strength, confirmed by the paired-samples t-test. There were significant differences (p-value < 0,05), indicating a change in BMI and an increase in strength. This supports the positive relationship between strength development and changes in students' BMI